1993
DOI: 10.1071/zo9930599
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Studies of the Intestinal Microflora of the Koala, Phascolarctos-Cinereus .1. Colonization of the Cecal Wall by Tannin-Protein-Complex-Degrading Enterobacteria

Abstract: The tannin-protein-complex-degrading enterobacterium (T-PCDE), which specifically colonises the caecal wall of the koala, was investigated immunohistologically. Polyclonal antisera were raised against three strains of T-PCDE. Tissue from six koalas was subjected to immunogold staining using a pooled, absorbed antiserum. Numerous T-PCDE cells were observed in the bacterial layer attached to the caecal wall of five of the animals. The distribution pattern of T-PCDE varied: cells were either scattered throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The koala is a monogastric hindgut fermenter with the largest relative cecal surface area of any species (Snipes et al, 1993). Hindgut fermenters are particularly susceptible to changes in the gastrointestinal microflora induced by antimicrobial therapy (Toutain et al, 2010), which is thought to be the reason for the inappetence and wasting observed following administration of macrolides and tetracyclines to koalas (Brown et al, 1984;Osawa et al, 1993). Thus, in the absence of clinical data demonstrating safety of high doses of enrofloxacin in koalas, increasing the dose sufficiently to enable attainment of these pharmacodynamic targets appears inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The koala is a monogastric hindgut fermenter with the largest relative cecal surface area of any species (Snipes et al, 1993). Hindgut fermenters are particularly susceptible to changes in the gastrointestinal microflora induced by antimicrobial therapy (Toutain et al, 2010), which is thought to be the reason for the inappetence and wasting observed following administration of macrolides and tetracyclines to koalas (Brown et al, 1984;Osawa et al, 1993). Thus, in the absence of clinical data demonstrating safety of high doses of enrofloxacin in koalas, increasing the dose sufficiently to enable attainment of these pharmacodynamic targets appears inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline, doxycycline or macrolides (such as azithromycin, clarithromycin, and erythromycin), and fluoroquinolones (such as ciprofloxacin) have been used to successfully treat chlamydiosis in people (Kohlhoff & Hammerschlag, ; Senn, Hammerschlag, & Greub, ); however, there are fewer options for koalas because erythromycin (dosage not documented) (Brown, Wood, & Dickens, ) or oxytetracycline (50 mg/kg of long‐acting formulation administered subcutaneously [s.c.] every 7 days, for a maximum of four injections) resulted in emaciation and death (Osawa & Carrick, ). It is suggested that some antibacterials, especially those with activity against anaerobic bacteria, affect the gastrointestinal tract (git) microbial flora of koalas resulting in dysbiosis (Osawa, Bird, Harbrow, Ogimoto, & Seymour, ). Dysbiosis was reported in five koalas when dosed with doxycycline at either 0.25 mg/kg twice daily, by mouth (p.o.…”
Section: Anti‐infectivesmentioning
confidence: 99%
“…Because these complexes are not readily degraded by mammalian digestive enzymes, presence of tannins adversely affects food digestibility and nutrient absorption (Hagerman & Klucher 1986;Mehansho et al 1987). Herbivores have evolved different strategies to avoid the adverse effects of ingested tannins, including the production of tannin-binding, proline-rich salivary proteins (Robbins et al 1991) and presence of symbiotic tannin-degrading bacteria in their gastrointestinal tract (Osawa et al 1993). Tannin acylhydrolase (tannase) can hydrolyze HTs to gallic acid and glucose (Aguilar et al 2007), so bacteria with tannase activity in the guts of herbivores aid in digesting these molecules for nutrient absorption (Osawa & Sly 1992;Nemoto et al 1995;Smith & Mackie 2004).…”
Section: Introductionmentioning
confidence: 99%